Fuzzy Inferensi System pada Produksi Kerupuk Lipat - Chalizah Nur Khasanah; Purnama Nuraini (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
Crackers are one of the favorite foods of Indonesian people which are made from flour mixture mixed with flavoring ingredients. UD.Eman is one of the factories that produces folding crackers. The instability of cracker orders which are sometimes high and sometimes low makes UD. Eman difficult in determining the amount of cracker production. These problems can be solved by using the Fuzzy Tsukamoto method by using 3 fuzzy variables, namely demand [x] where, inventory [y], production [z]. From the results of research conducted can produce clarity for the production of crackers per day. If the demand for 800 packs per day and stock of 500 packs per day, 947 packs of crackers can be produced per day.